A PERSONAL HEALTH RECORD MODULE FOR PREGNANT WOMEN: SYSTEM DEVELOPMENT AND USER ADOPTION STUDY - Sayyedi, Viand Kayvan (My University, 2014)
Pregnancy is one of the most important periods of a woman’s life, during which lots of potentially worrying changes occur in her body. Being aware of the nature of these changes can help her to make informed decisions and decrease her level of uncertainty and anxiety. Delivering information to pregnant women to help understand these changes is not a new idea. Brief searches of the web turned up many related resources and information. One important aspect of pregnancy that was found to be widely used was keeping daily records in a paper-based format. However, to the author’s best knowledge, there is no pregnancy specific electronic personal health record (ePHR) currently being used in Canada. In this study, a preliminary pregnancy specific PHR module was developed, and its usefulness and usability evaluated.
Keywords: Personal health records; Pregnancy; Smart device; usefulness; ease of use; technology acceptance model; Health Information Technology; Health Information Technology